Helminth infection modulates number and function of adipose tissue Tregs in high fat diet-induced obesity. - Camila P Queiroz-Glauss; Mariana S Vieira; Marcela Helena Gonçalves-Pereira; Stephanie S Almeida; Rachel H Freire; Maria A Gomes; Jacqueline I Alvarez-Leite; Helton C Santiago (Public Library of Science (PLoS), 2022)
Background Epidemiological and experimental studies have shown a protective effect of helminth infections in weight gain and against the development of metabolic dysfunctions in the host. However, the mechanisms Treg cells exert in the helminth-obesity interface has been poorly investigated. The present study aimed to verify the influence of Heligmosomoides polygyrus infection in early stages of high fat diet-induced obesity. Principal findings The presence of infection was able to prevent exacerbated weight gain in mice fed with high fat diet when compared to non-infected controls. In addition, infected animals displayed improved insulin sensitivity and decreased fat accumulation in the liver. Obesity-associated inflammation was reduced in the presence of infection, demonstrated by lower levels of leptin and resistin, lower infiltration of Th1 and Th17 cells in adipose tissue, higher expression of IL10 and adiponectin, increased infiltration of Th2 and eosinophils in adipose tissue of infected animals. Of note, the parasite infection was associated with increased Treg frequency in adipose tissue which showed higher expression of cell surface markers of function and activation, like LAP and CD134. The infection could also increase adipose Treg suppressor function in animals on high fat diet. Conclusion These data suggest that H. polygyrus modulates adipose tissue Treg cells with implication for weight gain and metabolic syndrome.